The Influence of Multiculturalism Education and Pancasila Student Profile on Religious Moderation of Students - Untu, Hadi Ignatius (Journal La Sociale, 2025)
This study aims to prove that religious moderation is an important and urgent matter among students. Religious moderation will be seen in relation to multicultural education and Pancasila student profile. This study was conducted at Karitas Tomohon Catholic High School with 205 students as respondents. This study is a causality study using a quantitative approach. Before the data was analyzed using multiple linear regression analysis, data normality, data linearity and data multicollinearity tests were first carried out. From the results of the data analysis, the R value was obtained as 0.688 and R² as 0.473 with a significance of 0.000. The results of this study indicate that there is a positive and significant influence of multicultural education and Pancasila student profile on religious moderation of Karitas Tomohon Catholic High School students.